The effect of intersecting sequential and random training according to learning and thinking patterns on the acquisition and retention of some offensive basketball skills for the student. Research extracted from the master’s thesis of the student Suhaib Mustafa Abdul Qadir. - غفور, توانا وهبي; عبدالقادر, صەيب مصطفى (Sulaimani Journal for Humanities, 2025)
This study aims at investigating the impact of impacts of practicing sequential random exercises depending on the educational and thought patterns (right and left) among three groups of university male students while learning basketball attacking drills. The study used a pretest-posttest design to figure out the differences between the participants while learning these drills. The participants of the study are 26 students who were in the second year of their bachelor degree program in the college of physical education at the University of Halabja for the academic year 2015- 2016. Descriptive and experimental techniques were used as data collection instruments for the purpose of the study. The researcher designed a special random exercise based on the educational and thought patterns of basketball skills such as (Handling over the head, hands, handling with one hand over the shoulder (long), clapotement low-lying, high clapotement, peaceful correction from the top, and free-throw shooting stability) to understand the experiences of the three groups of the students in terms of learning basketball attacking drills. The results of the study reveal that: 1. Sequential random exercises have positive effects on learning attacking skills in basketball of the three groups of the students as follow: a- third experimental group (serial random exercise according to the complete patterns). b- First experimental group (serial random exercise according to the right patterns) and the second experimental group serial random exercise according to the left patterns. 2. The three experimental groups have indicated an active role in the retention of attacking skill as follow: a- Third experimental group (serial random exercise according to the complete patterns). b- The second experimental group (serial random exercise according to the left patterns). c- The first experimental group (serial random exercise according to the right patterns).